Thoracic endovascular repair for acute type A aortic dissection: operative technique - Shah, Aamir; Khoynezhad, Ali (Annals of Cardiothoracic Surgery; Vol 5, No 4 (July 01, 2016): Type A Aortic Dissection (II), 2016)
Acute type A aortic dissection is a potentially lethal condition which requires immediate diagnostic and therapeutic intervention. Open surgical repair remains the standard of care as survival rates continue to improve in the modern surgical era. Unfortunately, up to twenty percent of patients are denied surgical therapy because they are deemed medically unfit to undergo open repair. The application of thoracic endovascular aortic repair (TEVAR) has changed the treatment paradigm for aortic disease involving the descending thoracic aorta and may be a viable rescue option for patients with type A dissection who are not eligible for open surgical repair. New endovascular devices and advanced image-guided procedures are continually evolving. This article summarizes the pathology of aortic dissection and focuses on currently available endovascular solutions for transapical and transfemoral stent graft deployment for acute aortic dissection involving the ascending aorta for selected patients who are ineligible for open surgical repair.